Tingkat Pengungkapan Pelaporan Keberlanjutan dan Kinerja Perusahaan - Walid Rudianti; Yenny Purbandari (Faculty of Economics and Business, University of Pancasakti Tegal, 2020)
The study of the impact of sustainability reporting on financial performance, corporate value and abnormal returns has been done. The quantitative approach is used to observe the impact. The population of this study are companies that issue sustainability reporting listed on the Bursa Efek Indonesia during the year 2013-2016. The sample of this study amounted to 32 taken with purposive sample method. Based on the results of a simple regression analysis for the effect of sustainability reporting on financial performance obtained adjusted R2 value of 15.9%. The effect of sustainability reporting on company value obtained adjusted R2 results of 9.6%. While for the sustainability reporting of abnormal returns, the probability value is 0.617> 0.05, which indicates that there is no effect of the continuous report.